2021
DOI: 10.1007/s00382-020-05563-1
|View full text |Cite
|
Sign up to set email alerts
|

Decadal change and inter-annual variability of net primary productivity on the Tibetan Plateau

Abstract: Net primary productivity (NPP) is an important indicator of plant dynamics and the net carbon exchange between the terrestrial ecosystem and atmosphere. Both the long-term shifts in climate mean (climate change) and short-term variations around the climate mean (climate variability) have impacts on NPP but studies examining both aspects of climate variations are rare especially in the data-scarce regions such as the Tibetan Plateau (TP). Here, we used a dynamic vegetation model to investigate the impacts of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
3
14
0
Order By: Relevance
“…The increase of NPP over the entire TP is consistent with Zhuang 2010) who found that the TP changed from a small carbon source or neutral state in the early part of the century to a carbon sink later on, which indicates improved ecosystem productivity with time. The great spatial heterogeneity in annual NPP change in the future on the TP is similar to that of the historical period which has been reported by Cuo et al (2021), C. Li et al (2022), andPiao et al (2012). Vegetation productivity change in the DPSZs on the TP is apparently opposite to that in the arctic and subarctic regions in the historical period.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The increase of NPP over the entire TP is consistent with Zhuang 2010) who found that the TP changed from a small carbon source or neutral state in the early part of the century to a carbon sink later on, which indicates improved ecosystem productivity with time. The great spatial heterogeneity in annual NPP change in the future on the TP is similar to that of the historical period which has been reported by Cuo et al (2021), C. Li et al (2022), andPiao et al (2012). Vegetation productivity change in the DPSZs on the TP is apparently opposite to that in the arctic and subarctic regions in the historical period.…”
Section: Discussionsupporting
confidence: 79%
“…For soil moisture, all of the correlation coefficients, with the exception of −0.02 at Ngari, are greater than 0.47 and RMSE ranges from 0.01 to 0.09 (Table S2 in Supporting Information ). These analyses and the evaluations conducted in previous studies (Cuo et al., 2016, 2020, 2021) all demonstrate that the performance of LPJ on the TP is in general reasonable.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The precipitation also increased significantly in much of TP (Zhao, Zhang, & Zhou, 2022) except the southern TP, where decreasing trend occurred (Yue et al., 2020). Meanwhile, vegetation greenness (Piao et al., 2015; Wei et al., 2022) and productivity (Cuo et al., 2021; Piao et al., 2012) overall enhanced in most parts of TP since a warmer and wetter climate can promote the growth of alpine plants. Because WUE serves as an integrated functional indicator of ecosystems (Hatfield & Dold, 2019), it is necessary to elucidate how WUE of Tibetan alpine grassland varies and what its major drivers are for a better understanding of the responses and feedbacks of high‐elevation ecosystems to a changing climate.…”
Section: Introductionmentioning
confidence: 99%
“…It is related to life activities such as vegetation growth, development, and reproduction, and it also provides an indispensable material basis for the life activities of other biological members in the entire ecosystem. Most of the studies focus on the spatiotemporal changes in NPP [13,14] and the impact of climate and human activities on NPP [15,16], modeling organic carbon storage with NPP as input data, and changes in carbon sources and sinks of the terrestrial ecosystem [12,[17][18][19]. Studies on the changes in NPP with increasing elevation gradients (EG) are mainly conducted in local regions, and all come from instantaneous surveys [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%